BRUTALISME OKNUM APARAT POLISI PADA MASA KINI DITINJAU DARI PERSEPEKTIF HUKUM DAN MORALITAS - Helsony Zelson; Davit Rahmadan; Tengku Arif Hidayat (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Irregular behavior of members of the Police is a violation of the Police professional code ofethics and Police disciplinary regulations. However, it is felt that law enforcement against theseregulations is still far from expectations and has not been able to maximally have a positive impacton the behavior of members of the Police, both due to the process of law enforcement and the resultsof law enforcement regulations. Efforts to enforce the code of ethics and disciplinary regulations areurgently needed in order to realize the implementation of assigned tasks and achieve policeprofessionalism. Based on this, the author is interested in discussing law enforcement againstmembers of the Police who commit irregularities, while the focus of his research is on members ofthe Police who commit abuse.This study aims to determine the forms of brutalism committed by police officers in carryingout their duties as law enforcement officers and to review the role of law enforcement police officersfrom a legal and moral perspective.The forms of brutalism are: physical violence, structural violence, and psychologicalviolence. Not only seen from the form, but brutalism can also be seen based on the perpetrators,namely: individual violence and collective violence.In the provisions of Article 13 it is emphasized that the Police are tasked with: 1.maintaining public order and security; 2. enforce the law; 3. provide protection, shelter and serviceto the community (Article 13, Law No. 2 of 2002).Keywords: Brutalism, Police, Law Enforcement.